Characterization of a promising luminescence-based graphite radiation dosimeter. (November 2021) - Mat Nawi, Siti Nurasiah; Khandaker, Mayeen Uddin; Bradley, D.A.; Sani, S.F. Abdul; Al-mugren, K.S.
Abstract: Characterization has been undertaken of the thermoluminescence (TL) properties of 0.3 mm polymer pencil lead graphite (PPLG). For 60 Co gamma irradiation doses from 0.5 Gy up to 20 Gy readout data have been taken at different heating rates, from 2 to 15 ° C s −1, linear TL responses with radiation dose being found, also with a greater degree of sensitivity at the lowest dose. Estimation has been made of the principal trap parameters of the PPLG, use being made of the variable heating rate method via the Hoogenstraaten, Booth - Bohun – Parfianovitch and Two Point Two Heating Rate techniques. Among the trap parameters are included the order of kinetics, activation energy, the frequency factor, and the initial concentration of trapped electrons. Also determined are relations that allow estimation of the temperature lag between the heating element and that of the sample. The stability of TL signal has been examined at peak temperatures with the lifetime of the TL glow peak calculated. Structural alterations of the irradiated PPLGs have been observed via Raman and Photoluminescence (PL) spectroscopy, also via X-ray diffraction (XRD), providing information on physical parameters relating to the defects participating in the luminescence process. The results indicate 0.3 mm PPLG to offer promising potential as a new generation of radiation dosimeter, including for medical radiation applications. Highlights: Novel use of 0.3 mm polymer pencil lead graphite for radiation dosimetry. Use was made of TL, Raman, PL and XRD techniques to characterize the samples. Principal trapping parameters was estimated to elucidate the effect of heating rate. Detailed physical parameters of defects involved in the TL process is reported. Declaration conflict of interest.